Case report: reinitiating pembrolizumab treatment after small bowel perforation - Tim N. Beck; Alexander E. Kudinov; Essel Dulaimi; Yanis Boumber (BMC Cancer, 2019)
Abstract Background Immune checkpoint inhibitors (ICIs) have emerged as paradigm shifting treatment options for a number of cancers. Six antibodies targeting the immune checkpoint proteins programmed cell death 1 (PD-1), programmed cell death 1 ligand 1 (PD-L1) or cytotoxic T-lymphocyte associated protein 4 (CTLA4) have been approved. In some cases, response rates have been impressive, but not uniformly so and not consistently; similarly, toxicity to this class of therapeutic is often unpredictable and can be life threatening. Predicting treatment response and toxicity are two main obstacles to truly individualize treatment with ICIs. One of the most severe and life-threatening adverse events is colitis induced colonic perforation, estimated to occur in 1.0 to 1.5% of patients treated with ICIs. An important question to address is, under what circumstances is it appropriate to reinitiate ICI treatment post-bowel perforation? Case presentation The patient is a 62-year-old woman, who presented with stage IV lung cancer. Immunohistochemical staining indicated that 80% of the patient’s tumor cells expressed PD-L1. The patient was started on a three-week cycle of pembrolizumab. Subsequent reducing in tumor burden was observed within ten weeks. Initially, pembrolizumab was tolerated fairly well, with the exception of immunotherapy related hypothyroidism. However, the patient experienced a second, more serious immune-related adverse event (irAE), in the form of enteritis, which led to small bowel perforation and necessitated exploratory laparotomy. The concerning part of the small bowel was resected, and a primary anastomosis was created. Based on the pathological and surgical findings, the patient was diagnosed with pembrolizumab-associated small bowel perforation. The patient recovered well from surgery and, considering the patient’s remarkable response to treatment, a collective decision was made to reinitiate pembrolizumab on post-operative day twenty-eight. The patient is continuing her immunotherapy with ongoing partial response and is able to continue her full-time job. Conclusions This case report highlights the challenges of identifying patients likely to respond to ICIs and those that are likely to experience irAEs and it discusses the impressive work that has been done to start to address these challenges. Lastly, the topic of reinitiating pembrolizumab treatment even after colonic perforation is discussed.